Improvement of Managerial Competence Based on Training and Integrative Leadership - Wicaksari, Erisa Aprilia; Sri Wartini; Andhi Wijayanto; Euis Soliha (Southeast Asian Business Review, 2025)
Leadership behavior and skills are essential in dealing with dynamic environmental changes and building the morale and motivation of organizational members to achieve high work productivity. Leadership capabilities are needed to improve managerial competencies that play a role in influencing, coordinating, and communicating effectively. Managerial competence also creates openness, appreciation, and attachment felt by employees, thereby increasing efficiency and collaboration within the organization. In addition, this competency helps individuals complete tasks faster, more precisely, and professionally, which ultimately supports the achievement of organizational goals. One of the important factors in supporting managerial competence is training and integrative leadership roles that can be facilitated by organizations, including higher education institutions. This research aims to encourage the improvement of the managerial competence of study program leaders through training and integrative leadership. Integrative leadership theory seeks to identify the behaviors and characteristics of effective leaders and how they can influence subordinates in certain situations. Integrative leadership is seen as a strategic approach to influence employees through the leader's ability to manage the organization dynamically and adaptively, creating a productive and harmonious work environment.